'Boots on the ground': walking in occupied Palestinian territory. Issue 6 (2nd November 2019) - Sellick, Patricia
ABSTRACT: Masar Ibrahim al-Khalil is a trail 330kms long in the Palestinian West Bank. The object of this research is the social 'nonmovement', to borrow a term from Asef Bayat, of walkers from the US and Europe and their Palestinian hosts. Based on her own experience of walking and on interviews with other international visitors, the author concludes that this social nonmovement connects places along the trail (and beyond), walkers to each other and the people they encounter, and plural narratives of affective solidarity. These findings unsettle the idea of securitized territorial solutions and invite the possibility of continuous, open geographies.